THE ROLE OF INTERNATIONAL PARTNERSHIPS AND GLOBAL ALLIANCES FOR SECURING CRITICAL RAW MINERAL SUPPLY CHAINS - ADRIAN LUCIAN KANOVIC; DANIEL BULIN (Global Economic Observer, 2025)
The global energy and digital transitions have significantly increased the demand for critical raw materials (CRMs) and exposed vulnerabilities in current supply chains. This paper investigates the geopolitical, economic, and environmental risks associated with the high concentration of CRM production and reserves in a limited number of countries and regions. The purpose of this study is to assess how international strategic partnerships can mitigate these systemic risks and ensure more secure, diversified, and sustainable access to key mineral resources. The objectives pursued include: mapping the global distribution of CRM reserves and production capacities; identifying key geopolitical and structural risks that threaten supply chain resilience; and analysing the most relevant international initiatives and bilateral or multilateral agreements aimed at cooperation on CRM. The study focuses in particular on the European Union’s strategic partnerships with countries such as Canada, Namibia, Australia, and Japan, as well as transatlantic and Indo-Pacific alliances involving the United States, Canada, Japan, and Ukraine.